Zooplankton of the Straits of Malacca, with emphasis on copepods and fish larvae in the vicinities of Jarak, Perak and Sembilan Islands - L.L, Chew; V.C., Chong; A.L, Ooi (Malaysian Journal of Science, 2008)
Zooplankton diversity and abundance of the Malacca Straits’ waters were assessed in the SESMA I and II research cruises from 4-9 June 2004 and 23-28 November 2007 respectively. In SESMA I, samplings of zooplankton in the waters of Pulau (=island) Jarak, Pulau Sembilan and Pulau Perak, were carried out by oblique tows using 45-cm diameter bongo nets of 180 µm and 363 µm mesh size. From the bongo net catches, the estimated mean wet biomass (± SD, g m-3) of zooplankton at Pulau Jarak, Pulau Sembilan and Pulau Perak were respectively 0.49 ± 0.22, 0.45 ± 0.10 and 0.16 ± 0.10 for the fine net, and 0.14 ± 0.04, 0.14 ± 0.10 and 0.10 ± 0.01 for the coarse net. For the same sites, the mean total zooplankton density (indiv. m-3), as estimated by the fine net, was 2 990 ± 1191, 14 242 ± 3441 and 1722 ± 460, respectively. For fish larvae, the mean density (indiv. 100 m-3) at these sites were 31.7 ± 6.7, 22.9 ± 16.5 and 26.3 ± 2.9, respectively. The main taxa of zooplankton were Copepoda, Urochordata, Ostracoda, Polychaeta and Mollusca. Copepods were represented by 71 identified species from 24 families, which were dominated by the Paracalanidae, Oithonidae, Oncaeidae, Corycaeidae and Euterpinidae. Fish larvae were represented by 24 identified families, the most abundant were from the Carangidae, Engraulidae, Gobiidae and Siganidae. However, the waters around the islands were not as rich in fish larvae (23 – 32 indiv. 100 m-3 ) as compared to the more open waters in the straits, where along a transect from Pulau Pangkor to Pulau Perak, the fish larval abundance sampled ranged from 38 – 274 indiv. 100 m-3. The light traps deployed in Pulau Jarak and Pulau Sembilan waters during SESMA II were not effective in sampling zooplankton due to swift water conditions during the study period. In Pulau Jarak waters, the main zooplankton attracted to the light traps were copepods (46.9%), followed by isopods (12%), Lucifer (9.7%), Oikopleura (6.6%), fish larvae (2.3%) and other crustaceans (15.1%). In Pulau Sembilan waters, Acetes (54.2%) dominated, followed by copepods (20.8%), ostracods (5.5%) and other crustaceans (13%). Taburan diversiti dan kelimpahan zooplankton di perairan Selat Melaka dikaji dalam penyelidikan perlayaran SESMA I dan II dari 4-9 Jun 2004 dan 23-28 November 2007 masing-masing. Dalam SESMA I, persampelan zooplankton di perairan Pulau Jarak, Pulau Sembilan dan Pulau Perak dilakukan secara serong dengan menggunakan sebuah pukat bongo yang bermulut 45 cm diameter, dengan mata jaring yang bersaiz 180 µm dan 363 µm. Dari tangkapan pukat bongo, anggaran min biomass basah (± SD, g m-3) zooplankton di Pulau Jarak, Pulau Sembilan dan Pulau Perak adalah masing-masing 0.49 ± 0.22, 0.45 ± 0.10 dan 0.16 ± 0.10 bagi pukat halus, dan 0.14 ± 0.04, 0.14 ± 0.10 dan 0.10 ± 0.01 bagi pukat kasar. Bagi tempat yang sama, purata densiti jumlah zooplankton (indiv. m-3) adalah 2 990 ± 1191, 14 242 ± 3441 dan 1722 ± 460 masing-masing. Purata densiti larva ikan adalah masing-masing 31.7 ± 6.7, 22.9 ± 16.5 dan 26.3 ± 2.9 bagi tempat tersebut. Taxa zooplankton yang utama adalah Copepoda, Urochordata, Ostracoda, Polychaeta dan Mollusca. Copepoda diwakili oleh 71 spesies dari 42 famili, yang didominasi oleh Paracalanidae, Oithonidae, Oncaeidae, Corycaeidae dan Euterpinidae. Larva ikan diwakili oleh 24 famili, dengan kelimpahan tertinggi daripada Carangidae, Engraulidae, Gobiidae dan Siganidae. Kelimpahan larva ikan di perairan pulau-pulau adalah lebih rendah (23 – 32 indiv. 100 m-3 ) jika dibandingkan dengan perairan terbuka sepanjang transek daripada Lumut ke Pulau Perak (38 – 274 indiv. 100 m-3). Perangkap cahaya yang digunakan di perairan Pulau Jarak dan Pulau Sembilan semasa SESMA II adalah tidak efektif bagi penyampelan zooplankton disebabkan oleh keadaan arus yang deras semasa pensampelan. Di perairan Pulau Jarak, zooplankton utama yang tertarik kepada perangkap cahaya adalah kopepod (46.9%), diikuti oleh isopod (12%), Lucifer (9.7%), Oikopleura (6.6%), ikan larva (2.3%) dan krustasea lain (15.1%). Di perairan Pulau Sembilan, Acetes (54.2%) mendominasi, diikuti oleh kopepod (20.8%), ostrakod (5.5%) and krustasea lain (13%).